Child perceptions questionnaire 11-14 in Turkish language in an orthodontic patient sample - Dilruba Sanya Sadıkzade; Arzu Alagöz; Ahmet Can Yılmaz; Cihan Aydoğan (Istanbul University, 2018)
DOI: 10.26650/eor.2018.07379Purpose The Child Perceptions Questionnaire 11-14 (CPQ 11-14) is a generic tool that was developed to measure oral health-related quality of life in early adolescents. The aim of this study was to prepare a Turkish version of the CPQ 11-14 and to test its psychometric properties in an adolescent orthodontic patient sample. Materials and Methods The questionnaire was adapted to Turkish using a forward backward translation method, and it was found to be understandable in a pilot study (n=15). The Turkish version of the CPQ 11-14 was administered to 200 orthodontic consultation patients (aged 11-14 years). Retests were conducted in 50 patients 2 weeks after the first tests. The ICON index was used to determine the orthodontic treatment need. Decayed, missing, and filled teeth were also recorded with the DMFT index. Spearman correlations and t-tests were used to assess validity. Internal consistency was assessed using Cronbach's alpha coefficient, and intraclass correlation coefficients were calculated to assess test-retest reliability. Results Significant positive correlations were found between CPQ 11-14 scores and the global ratings of oral health (r=0.381), global ratings of well-being (r=0.350), ICON scores (r=0.211), and DMFT scores (r=0.233), supporting construct validity. Children who needed orthodontic treatment had a worse quality of life than those who did not need orthodontic treatment (p=0.016). Cronbach's alpha and intraclass correlation coefficients were calculated as 0.917 and 0.817, respectively, demonstrating good internal consistency and acceptable test-retest reliability. Conclusion The Turkish version of the CPQ 11-14 was found to be valid and reliable in 11-14-year-old orthodontic patients.